Der brasilianische Blick : Um olhar brasileiro : Sammlung Gilberto Chateaubriand / MAM - RJ. - Haus der Kulturen der Welt, Berlin; Ludwig Forum für Internationale Kunst, Aachen; Kunstmuseum Heidenheim, Heidenheim; Bezerra, Vauluizo; Canongia, Ligia; Chateaubriand, Gilberto; Cocchiarale, Fernando; Diepgen, Eberhard; Hegyi, Lóránd; Herkenhoff, Paulo; Hirner, René; Kandel, Susan; et al. (Berlin : Deutsch-Brasilianische Kulturelle Vereinigung, 1998)
Romagnolo, Sergio ; Leirner, Jac ; Meireilles, Cildo ; Tunga ; Prolik, Eliane ; Resende, José ; Caldas, Waltercio ; Gomes, Fernanda ; Ruiz, Mauricio ; Emanuel, Jorge ; Soares, Valeska ; Guagliardi, Carla ; Bechara, José ; Barreto, Lia Menna ; Catunda, Leda ; Barrão, Jorge ; Flemming, Alex ; Duarte, Jorge ; de Souza, Edgard ; Zerbini, Luiz ; Senise, Daniel ; Varejao, Adriana ; Milhazes, Beatriz ; Canale, Cristina ; Abreu, Marcia ; André, Marcus ; Almeida, Efrain ; Pereira, Paula ; Pizarro, Luiz ; de Castro, Hildebrando ; Barends, Nathalie Petsiré ; Rio Branco, Miguel ; Weidle, Carina ; Muniz, Vik ; Tschäpe, Janaina ; Bernadelli, Enrica
Der brasilianische Blick : Um olhar brasileiro : Sammlung Gilberto Chateaubriand / MAM - RJ, Haus der Kulturen der Welt, Berlin, 03.07.1998 - 13.09.1998 / Ludwig Forum für Internationale Kunst, Aachen, 22.10.1998 - 29.11.1998 / Kunstmuseum Heidenheim, 13.12.1998 - 31.01.1999
Duits & Engels
Duits & Portugees
boek
Keywords: Brazilië